Trans legal parenthood in the Nordic countries: between biogenetics and lived experience - Alaattinoğlu, Daniela; Margaria, Alice (Oxford University Press, 2026)
Trans legal parenthood has been litigated before several European courts over the past decade. Yet the prevailing European legal approach remains one of gender misalignment, whereby parental status is assigned according to the parent’s birth-assigned gender rather than their legally recognized gender. With the exception of Norway, the Nordic countries stand out as a notable divergence. By embracing a gender-alignment approach to parental determination, they make visible and critically challenge the often cisnormative and heteronormative assumptions underpinning the legal regulation of parenthood. While moving in the same general direction, the Nordic jurisdictions have nonetheless adopted distinct paths in regulating trans parenthood over the past several years, ranging from gender misalignment (Norway), to particularizing alignment (Sweden, Denmark, and Finland), and pluralistic alignment (Iceland). This article investigates and compares these different models, contributing original insight by foregrounding the varying emphasis each country places on notions of biogenetics, lived experience, and gender in the regulation of trans legal parenthood. Despite their differences, the approaches reveal an uneasy yet pragmatically managed coexistence of biogenetic and social aspects of parenthood, alongside the persistent gendered nature of legal parenthood and its regulation.